Perbandingan Dinamika Kelembagaan Ekonomi Islam di Pakistan dan Inggris: Perspektif Peran Regulasi dan Inovasi Produk - Silvia Dea Lova; Naufal Luthfi Alifa (Yayasan Literasi Sains Indonesia, 2025)
This study aims to comparatively analyze the dynamics of Islamic economic institutions in Pakistan and the United Kingdom, focusing on evaluating major challenges and formulating adaptive and innovative institutional strengthening strategies to promote stability and inclusion in Islamic finance, while providing applicative reflections for sustainable economic development in Indonesia. The research employs a qualitative approach with comparative and descriptive study design, involving data collection through literature review and thematic content analysis to ensure validity through triangulation. Key findings reveal that in Pakistan, Islamic economic institutions develop through low-risk Sharia mutual funds and Islamic banking with strong liquidity but face challenges of low profitability due to non-performing loans and limited instruments; whereas in the UK, regulatory support and product innovations like sukuk drive growth, despite challenges in public literacy and infrastructure. The interpretation of results emphasizes integrating regulatory strengthening, product innovation, and literacy enhancement as primary strategies, concluding that this comparative model can serve as a foundation for developing Islamic economics in Indonesia that supports sustainable, inclusive, and socially-environmentally oriented MSMEs.